Being moved: how do attachment styles and emotion regulation affect the experience of being moved? - Miguel, Rita Ramos (2016)
This work intends to contribute to the empirical body of research on positive emotions in general, having a particular interest in the emotional experience of being moved or touched. The being moved experience was also explored with attachment and emotion regulation strategies (reappraisal and suppression). A sample of Portuguese and Norwegian participants (aged 18 to 66 years old) was collected through an online procedure resulting in a total of 387 answers from the general population. The emotional experience of being moved was elicited by three different videos (presented randomly and previous tested) and manipulated by different instructions that asked participants different emotion regulation strategies – no instructions, reappraisal instructions and suppression instructions. After each movie participants answered a being moved scale and an attachment scale was also rated. Results suggest a significant relation between being moved and the manipulation of emotion regulation strategies (reappraisal and suppression). Reappraisal and suppression downregulate the experience of being moved and tears (comparing with no instructions regarding to emotion regulation strategies). Comparing both emotion regulation strategies, reappraisal downregulates more the being moved experience and tears than suppression. On the other hand, an anxiety attachment style proved to be significant and positively correlated with experiences of being moved as well as with feelings of choking up and tears. Nationality is also an important variable predicting being moved experiences. The comparison between the Portuguese and Norwegian samples showed significant differences in how participants feel touched. Results showed that Portuguese participants reported higher levels of being moved, higher levels of tears and feeling choked up, but lower level of feeling a warmth in their chest. In general, the being moved experience and their bodily sensations are sensitive to emotion regulation activity and to the attachment styles.